Detection of Victoria lineage influenza B viruses with K162 and N163 deletions in the hemagglutinin gene, South Africa, 2018. Issue 3 (17th September 2021) - Hellferscee, Orienka; Treurnicht, Florette; Gaelejwe, Lucinda; Moerdyk, Alexandra; Reubenson, Gary; McMorrow, Meredith; Tempia, Stefano; McAnerney, Johanna; Walaza, Sibongile; Wolter, Nicole; von Gottberg, Anne; Cohen, Cheryl
Abstract: Background: A group of Victoria lineage influenza B viruses with a two amino acid deletion in the hemagglutinin (HA) at residues K162 and N163, was detected during the 2016 to 2017 Northern Hemisphere influenza season and continues to spread geographically. We describe the first identification of viruses with these deletions from South Africa in 2018. Methods: Nasopharyngeal samples were obtained from the syndromic surveillance programs. Real‐time reverse transcription‐polymerase chain reaction was used for virus detection and lineage determination. Influenza genetic characterization was done using next‐generation sequencing on the MiSeq platform. The duration of virus circulation was determined using thresholds calculated using the Moving Epidemic Method; duration was used as an indicator of disease transmissibility and impact. Results: In 2018, 42% (426/1015) of influenza‐positive specimens were influenza B viruses. Of 426 influenza B‐positive samples, 376 (88%) had the lineage determined of which 75% (283/376) were Victoria lineage. The transmissibility of the 2018 South African influenza season was high for a few weeks, although the severity remained moderate through most of the season. The sequenced 2018 South African Victoria lineage influenza B viruses clustered in sub‐clade V1A.1 with the 162‐163 deletions. Conclusions: We report the first detection of the 162‐163 deletion variant of influenza B/Victoria viruses from South Africa in 2018, and suggest that this deletion variant replaced the previous circulating influenza B/Victoria viruses. These deletions putatively affect the antigenic properties of the viruses because they border an immune‐dominant region at the tip of the HA. Therefore, close monitoring of these newly emerging viruses is essential.